PENGEMBANGAN EKONOMI RAKYAT MELALUI KOPERASI UNTUK PENANGGULANGAN KEMISKINAN DAN KONTRIBUSINYA DALAM PDRB PROVINSI MALUKU - Muspida Muspida; Maryam Sangadji (Jurnal Cita Ekonomika, 2018)
This study examines the development of cooperatives in reducing poverty and the impact on the regional economy over the past 10 years. The results obtained that the development of cooperative business volumes show a significant decrease in poverty rate and contribute to the increasing GDP.